Slope stability analysis in Ulubelu Lampung using computational analysis program - Jafri, M.; Iswan, Iswan; Rizki, M.; Susilo, G.E. (Civil and Environmental Science Journal (CIVENSE), 2020)
Ulubelu sub-district is the center of geothermal activity in Lampung Province. The Ulubelu geothermal project supply 25% of electricity to Lampung Province. In the future the Government plans to build a geothermal pipeline network with the aim of maximizing the potential found in Ulubelu. One of the objects that must be examined in the construction of the pipeline is the stability of the slope that will be passed by geothermal pipes. Therefore, this study aims to analyze the stability of landslides in the Ulubelu geothermal pipeline. Soil samples for this study were taken from 5 locations: BH-01, BH-02, BH-03, BH-04, and BH-05. This soil sample is then examined to determine its soil mechanics characteristics in the laboratory. The safety factor of each sample is analyzed using 3 slope analysis methods: the Fellenius method, the Bishop method, and the Janbu method, and calculated in Geostudio (Slope/W). The results showed that all samples showed safety factor values that were not much different that were spread between the numbers 1.7 to 4.3. This shows that all sample locations are safe from landslides. This also shows that the characteristics of the soil and the slope of the study area are almost the same.